2015
DOI: 10.1175/waf-d-14-00057.1
|View full text |Cite
|
Sign up to set email alerts
|

Climatology and Ensemble Predictions of Nonconvective High Wind Events in the New York City Metropolitan Region

Abstract: Damaging wind events not associated with severe convective storms or tropical cyclones can cause significant problems with transportation, infrastructure, and public safety over the northeastern United States. These nonconvective wind events (NCWEs) are difficult to forecast in New York City and surrounding regions as revealed by the relatively poor probability of detection (POD) and false alarm ratio (FAR) in recent years. This paper investigates the climatology of NCWEs between 15 September and 15 May over 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Milrad et al [19] suggested that along the east coast, extreme precipitation events are associated with nor'easters, while Sisson and Gyakum [20] suggested that over inland areas, heavy precipitation events are more related with cyclones from the southwest. Extreme wind events over the northeast are generally associated with storms from the southwest with the cyclone center to the west of the affected regions [21][22][23], while Colle et al [18] suggested that moderate storm surge events at New York City are mainly caused by nor'easters.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Milrad et al [19] suggested that along the east coast, extreme precipitation events are associated with nor'easters, while Sisson and Gyakum [20] suggested that over inland areas, heavy precipitation events are more related with cyclones from the southwest. Extreme wind events over the northeast are generally associated with storms from the southwest with the cyclone center to the west of the affected regions [21][22][23], while Colle et al [18] suggested that moderate storm surge events at New York City are mainly caused by nor'easters.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…High winds during the cool season can be separated in pre-cold frontal (PRF), post-cold frontal (POF), and strong pressure gradients near a coastal northeast winter storm (NEC). Layer and Colle (2015) showed that NECs and PRFs peak in December, while POFs peak in January and February. During the warm season, there can be severe small-scale convective wind gusts (Colle et al, 2012), quasi-linear convective systems and squall lines (Lombardo and Colle, 2010), and tropical cyclones undergoing extratropical transition such as Sandy (2012; Colle et al, 2015) andFloyd (1999;Colle, 2003).…”
Section: Recommendations For Researchmentioning
confidence: 99%
“…Near‐surface wind gusts are micro‐scale flow features typically resulting from downward entrainment of higher momentum air. They can be embedded within synoptic‐scale phenomena such as extra‐tropical cyclones (Earl et al., 2017; Layer & Colle, 2015; Letson et al., 2021), synoptic to mesoscale phenomena such as tropical cyclones (Shu et al., 2015; Sparks, 2003), be caused by topographically forced wave breaking or flow channeling (Letson et al., 2019; Ngo & Letchford, 2008), or result from meso‐to micro‐scale phenomena such as intense down‐drafts within deeply convective systems (Kuchera & Parker, 2006; Nakamura et al., 1996). While these parent phenomena are fully or partially resolved in most numerical weather prediction (NWP) and regional climate models, wind gusts themselves and the turbulent flow fields in which they are embedded are sub‐grid scale.…”
Section: Introductionmentioning
confidence: 99%